Agricultural Production and Transport Connectivity : Evidence from Mozambique - Iimi, Atsushi (World Bank, Washington, DC, 2021)
Despite the richness of the existing literature, it remains a challenge to find rigorous evidence of the impacts of transport connectivity on agricultural production. The paper aims at contributing to the prolonged debate on the transport-agriculture nexus in Africa, by taking advantage of the unique circumstances in Mozambique where the government intensively invested in road infrastructure during a relatively short period of time in the 2010s. With the highly disaggregated location-specific fixed-effects and instrumental variable technique used to control for the endogeneity issue, the paper shows that the improved road connectivity increased agricultural production significantly. In particular, access to domestic markets is found to be important. It is also found that agricultural production exhibits decreasing returns to scale, heavily depending on land input.